Preoperative nutritional status and obesity are associated with muscle atrophy and fatty infiltration in degenerative rotator cuff tears - Li Cen; Kun Tao; Hua Liu; Ming Li; Yun-Feng Zhang; Zhe-Yu Huang (Journal of Orthopaedic Surgery and Research)
Abstract Background Rotator cuff tear is a degenerative condition that has been previously linked to metabolic factors such as obesity and diabetes. However, the relationship between patients’ nutritional status and rotator cuff pathology remains unclear. Method We retrospectively reviewed data from patients with degenerative rotator cuff tears who underwent arthroscopic rotator cuff repair at our institution between June and December 2024. Collected variables included demographic characteristics, imaging findings, and biochemical markers indicative of nutritional status, such as hemoglobin, total lymphocyte count, serum albumin, prealbumin, and transferrin. The prognostic nutritional index (PNI) was calculated based on lymphocyte count and serum albumin levels. Patients were stratified based on the presence or absence of muscle atrophy and fatty infiltration, and intergroup comparisons were performed. Age-adjusted logistic regression was used to identify risk factors associated with muscle atrophy and fatty infiltration. Results A total of 109 patients met the inclusion criteria. Significant differences in age, obesity, hemoglobin, PNI, and albumin levels were observed between patients with and without muscle atrophy (all P < 0.05). Similarly, age, obesity, hemoglobin, lymphocyte count, and albumin were significantly associated with fatty infiltration (P < 0.05). After adjusting for age, obesity was associated with lower odds of muscle atrophy (OR = 4.581) and fatty infiltration (OR = 4.178). Decreased hemoglobin levels were associated with increased risk of muscle atrophy (OR = 0.954) and fatty infiltration (OR = 0.968). Lower PNI was also associated with muscle atrophy (OR = 0.822) and fatty infiltration (OR = 0.801), and reduced serum albumin levels were linked to higher odds of both outcomes (OR = 0.785 and 0.815, respectively). Conclusion Obesity and poor nutritional status may be significant risk factors for muscle atrophy and fatty infiltration in patients with rotator cuff tears. Level of evidence Level IV.